The mediating role of job motivation in the relationship between work conscience and productivity of female teachers - Derakhshandeh, Mansoor; Liaghat, Nahid; Karimi Sakha, Kolsoom; Mahdavipour, Mahdi; Delbaznasab, Simin; Shafaei, Nosrat (Psychology of Woman Journal, 2020)
This research was conducted to explain the mediating role of job enthusiasm in the relationship between work conscientiousness and the productivity of female teachers. The research design was descriptive and correlational. The statistical population of the research was formed by all the female teachers in the urban area of Yasouj city in 2019. Among the statistical population, 252 female teachers were selected and studied by multi-stage cluster random sampling. The Job enthusiasm questionnaire of Salanova and Schaufeli, Hersey et al.’s productivity, and Costa and McCree’s work conscientiousness questionnaire were used to collect data. After collecting and extracting the data, the participants’ scores were analyzed using Pearson’s correlation, multiple and multivariate linear regression, and the macro bootstrap test. The results showed a significant relationship between productivity and job enthusiasm (powerfulness, dedication, and absorption). There is a significant relationship between job enthusiasm and reliability component and success orientation. A significant relationship was also obtained between work conscientiousness and its components (reliability and success orientation) with job productivity. Also, the findings showed that job enthusiasm significantly mediates the relationship between work conscientiousness and the productivity of female teachers.